Effects of environmental factors and fermentation on red raspberry anthocyanins stability. (1st January 2023) - Yuan, Youwei; Tian, Yiling; Gao, Shuang; Zhang, Xuemei; Gao, Xufang; He, Junping
Abstract: In order to research on the effect of changes in anthocyanins on raspberry products color during fermentation, juice process and preservation, based on μ-HPLC/MS/MS analysis，Cyanidin-3-O-sophoroside, cyanidin-3-O-rutinoside, and cyanidin-3-O-glucoside were the predominant anthocyanins in red raspberry. In contrast, delphinidin-3-O-β-D-glucoside, cyanidin-3-O-glucoside, malvidin-β-d -glucopyranoside, and peonidin-3β-D-glucoside were the main anthocyanins in grape. After UV irradiation, loss rate of anthocyanins contents in raspberry was over 700 g/kg, while that in grape was around 450 g/kg. Considering heat treatment at 100 °C for 8 h, raspberry anthocyanins were basically completely degraded, whereas grape anthocyanins were still retained in small amounts. Moreover, the presence of oxygen at different concentrations led to a greater loss rate of anthocyanins in raspberry than in grape. Furthermore, the increase of total anthocyanins content in raspberry was lower during fermentation compared to grape, while the decrease in the content of main anthocyanins in raspberry was more remarkable than in grape. In addition, six possible oxidation products of anthocyanins pyrolysis were identified in raspberry wine, namely protocatechuic acid, sinapic acid, caffeic acid, gentisic acid, and salicylic acid; in contrast, ferulic acid, caffeic acid, and syringic acid were detected in grape wine. Collectively, anthocyanins in raspberry had lower stability than those found in grape under natural conditions or during fermentation. Highlights: Red raspberry Anthocyanins basic ingredients are C3S, C3R, and C3G. Temperature and pH are important elements of affecting raspberry anthocyanins stability. The pathway of raspberry anthocyanins degradation was discussed.